The Legality of “Taking” Colonial Cultural Property: Special Reference to the Period of Dutch Occupation in Sri Lanka - Madhushan, G.P.D.; Kamardeen, N. (University of Colombo, 2024)
Recent demands for, and return of, cultural objects taken during colonial occupation, have raised several questions that have not been satisfactorily answered yet. Primary among these is the basis for return. While early requests (such as those made by Hemasiri de Silva on behalf of Sri Lanka), focused on the importance of the object to the home state, the host states have been more concerned with the provenance of the object itself. The return of colonial cultural property thus far has not satisfactorily considered the legality of the taking, rendering the returns made so far rather ad hoc. Acquisition during colonial times has taken place through various means, and discerning the legality of these means is difficult due to the ambiguous and often contested legal norms that were operational at the time. Contemporary thinking on the legality of the actions of the colonial era has added a further layer of complexity to this issue. In the context of the return by the Dutch government to Sri Lanka of certain colonial cultural objects in 2023 in keeping with the Dutch Restitution Policy, this research will investigate the legality of the taking of colonial cultural property during the Dutch period of occupation of Sri Lanka. It will do so through an examination of the legal system in operation...
Keywords: Colonial Cultural Property; Legality; Dutch Restitution Policy; Restitution; Taking